User Guide to the G+ Product Profile Query Tool (G+ PP) - Ashby, Jacqueline A.; Polar, Vivian (International Potato Center, 2021)
This is a decision-support tool for assessing the gender-responsiveness of potential or actual breeding products (plant varieties and breeds of animals) for a defined segment of customers or users of the product. Men and women often have different roles and responsibilities in farming and agro-value chains, so they often need varieties that perform differently, requiring different traits in a new variety. You can use this tool to find out if you already have enough information to assess a breeding product for the customer segment of interest, or, if you don’t, the tool will identify precisely, what additional information you will need to find. After identifying the relevant gender “gaps” that influence adoption of plant varieties (or animal breeds) in the target customer segment, and gendered trait preferences, this tool generates a gender impact score based on analyses of “do no harm” and “positive benefit” for each trait of interest in a breeders’ product profile. The score summarizes the tool’s analysis of potential advantages and disadvantages of an actual orfuture variety formen and women. A breeding team, made up of plant breeders and social scientists, will use this tool to identify how a set of proposed traits will be harmful or beneficial to men and women and the trade-offs between different breeding objectives that this involves. The tool provides a questionnaire that requires answers in the form of expert judgments that should be supplied jointly by a social scientist experienced in using gender analysis and a breeder familiar with market-led breeding approaches. The G+ Product Profile Tool is meant to be used with the G+ Customer Profile Tool.